(3jJjeI GdYbhO GdhSWi aj efGbH SjOj GdeYWis - (3eMeO Hf YHO GdcQje GdYjOhfj, GdYjOhfj,J (B1189 (3g` s
(3ChdgG (B:s
(3jJjeI GdYbhO GdhSWi dJdejPg heeG Medfi Ydi JbjjO Pdc EXgGQkG dTcQ Gddg , hSejJg jJjeI GdYbhO GdhSWi ai efGbH CHj YHOGddg SjOi eMeO GdeYWi s
(3BNQgG (B:s
(3hGTJZd HGdPcQ MJi ZGH Yf MSg, ceG gi YGOJg eY ehdGg aCJh dg HGdWjH, hCRdgG ai Jdc GdMGd, ade jTYQ s
(3Odjd eDQN GdeZQH U`(B281s
(3hgh aj efGbH CHj YHOGddg eMeO GdeYWj Hf eMeO UGdM GdTQbhj GdYeQGhj GdeJGhaj SfI (B1180 (3g`s
(3hhGdOg GdTjN eMeO UGdMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B216s
(3Odjd eDQN GdeZQH (B- (3U (B281 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B479 s
Keywords: (3GdJGQjNs